Serbia’s foreign policy approach between strategic indeterminacy and the operationalization of the “four pillars” doctrine - Stanković, Nevena; Dabić, Dragana (International Problems, 2026)
In the absence of a codified strategic document, the foreign policy orientation of the Republic of Serbia can be more clearly observed through the patterns of its positioning vis à vis leading global actors, as well as through its responses to the pressures of the international system. This paper analyzes the aspects that have been shaping Serbia’s current foreign policy approach, with the aim of identifying the dominant pattern of its strategic behavior and assessing its operational scope. Based on the identified determinants of foreign policy, the research examines how these factors determine the choice, combination and operationalization of the state’s strategic options. The central hypothesis of the paper is that over the past two decades, the hedging strategy—operationalized through the “four pillars” policy—has been profiled as the dominant pattern of Serbia’s foreign policy behavior due to its high adaptability to growing geopolitical uncertainty and shifting distribution of power. Empirical findings confirm that the combination of strategic ambiguity, selective alignment, and indirect balancing—alongside the effort to protect foreign policy autonomy and the imperative of protection territorial integrity—constitutes the operational core of Serbia’s contemporary foreign policy approach. Particular analytical attention is devoted to the issue of Kosovo and Metohija, conceptualized as a key determinant and intervening variable in understanding how Serbia operationalizes its foreign policy conduct, adapts to external pressures and defines the boundaries of its strategic orientation toward major global actors. The final section problematizes the sustainability of the hedging strategy in current international circumstances, particularly in the period following 2022. In conclusion, the article demonstrates that hedging—while functional and adaptive under conditions of multipolarity—remains strongly conditioned by the structural constraints of the international system and the unresolved status issue of Kosovo and Metohija. Together, these factors define the limits of Serbia’s foreign policy autonomy and shape the framework of its future strategic practice.